The Role of Job Burnout on the Effect of Workload to Employee Performance at PT. Semen Indonesia Logistik - Muhammad Fikri Fachrudin; Hesty Prima Rini (Digital Innovation : International Journal of Management, 2025)
The intention of this research is to examine the impact of workload on employee performance of PT. Semen Indonesia Logistik by using job burnout as an intervening variable. This research uses quantitative research methods. The research participants were employees at PT. Semen Indonesia Logistik. Determination of the sample using saturated sample technique as many as 37 employees. Data collection using questionnaires distributed to employees. Statistical analysis of Structural Equation Modeling (SEM) Partial Least Squares 4.0 was used to test the hypothesis. Based on the research results, workload has a significant negative effect on employee performance. Workload also has a considerable impact on employee performance due to job burnout.